Styles, standards and meaning - Meyerhoff, M; Abtahian, MR; Gafter, RJ; Horesh, U; Kasstan, JR; Keegan, P; King, J (John Benjamins Publishing, 2021)
Style, in the study of variation and change, is intimately linked with broader questions about linguistic innovation and change, standards, social norms, and individual speakers’ stances. This article examines style when applied to lesser-studied languages. Style is both (i) the product of speakers’ choices among variants, and (ii) something reflexively produced through the association of variants and the social position of the users of those variants. In the context of the languages considered here, we ask “What questions do we have about variation in this language and what notion(s) of style will answer them?” We highlight methodological, conceptual and analytical challenges for the notion of style as it is usually operationalised in variationist sociolinguistics. We demonstrate that style is a useful research heuristic which – when marshalled alongside locally-oriented accounts of, or proxies for “standard” and “prestige”, in apparent time – allows us to describe language and explore change. It is also a means for exploring social meaning, which speakers may have more or less conscious control over.